2003
DOI: 10.1038/sj.bjc.6600999
|View full text |Cite
|
Sign up to set email alerts
|

First-line sequential high-dose VIP chemotherapy with autologous transplantation for patients with primary mediastinal nonseminomatous germ cell tumours: a prospective trial

Abstract: To determine the efficacy of first-line sequential high-dose VIP chemotherapy (HD-VIP) in patients with primary mediastinal nonseminomatous germ cell tumours (GCT), 28 patients were enrolled on a German multicentre trial. High-Dose VIP chemotherapy consisted of 3 -4 cycles of dose-intensive etoposide and ifosfamide plus cisplatin, q22days, each cycle followed by autologous peripheral blood stem cell transplantation plus granulocyte-colony stimulating factor (G-CSF) support. One cycle of standard-dose VIP was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 41 publications
0
17
0
1
Order By: Relevance
“…Despite the fact that the only randomized phase III study in ''intermediate'' and ''poor prognosis'' patients did not demonstrate a survival advantage for patients treated with primary high-dose chemotherapy and subsequent autologous stem cell transplantation compared to standard-dose chemotherapy (Motzer et al 2007), a number of non-randomized phase II clinical trials of the German Testicular Cancer Study Group have demonstrated excellent survival rates of up to 70-80% with first-line high-dose chemotherapy Bokemeyer et al 1999Bokemeyer et al , 2003Hartmann et al 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Despite the fact that the only randomized phase III study in ''intermediate'' and ''poor prognosis'' patients did not demonstrate a survival advantage for patients treated with primary high-dose chemotherapy and subsequent autologous stem cell transplantation compared to standard-dose chemotherapy (Motzer et al 2007), a number of non-randomized phase II clinical trials of the German Testicular Cancer Study Group have demonstrated excellent survival rates of up to 70-80% with first-line high-dose chemotherapy Bokemeyer et al 1999Bokemeyer et al , 2003Hartmann et al 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Bone marrow is affected by chemotherapy and regains the functions with ASCT. Bokemeyer et al [15] reported that according to "International Germ Cell Tumor Group Consensus Classification" the patients in the middle and poor prognosis groups benefit from high-dose chemotherapy and ASCT as a first treatment, instead of the standard treatment and the survey increases by %15. In this case, surgical excision followed by VIP chemotherapy and pathologic examination showed immature teratoma including 30%-40% necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous stem cell transplantation following high-dose chemotherapy is defined as a treatment option for selected patients [8,15,16]. Bone marrow is affected by chemotherapy and regains the functions with ASCT.…”
Section: Discussionmentioning
confidence: 99%
“…1 Recent medical efforts to treat such poor risk patients, including high-dose chemotherapy (HDCT) along with autologous peripheral blood stem cell (PBSC) support, have resulted in improved outcomes, although results are preliminary. [2][3][4] However, management of patients with residual cancer and poor prognoses after HDCT has not been well addressed. Here, we report a case of disseminated germ cell cancer successfully treated with intensive cisplatin-based standard-dose chemotherapy after first-line HDCT.…”
Section: Introductionmentioning
confidence: 99%